Surgery for Solid Pseudopapillary Neoplasm: Observational Study at a Nepalese Tertiary Center - Sah, Dhruba N; Bhandari, Ramesh S; Kansakar, Prasan BS; Ghimire, Bikal; Joshi Lakhey, Paleswan (Journal of Institute of Medicine Nepal, 2023)
Introduction Solid pseudopapillary neoplasms (SPN) are rare, relatively indolent tumors with potential malignant behavior. The incidence of these tumors is increasing due to the widespread use of cross-sectional imaging. This study aimed to analyze the clinicopathological details, surgical management, and short- and long- term outcomes of operated cases of SPN. Methods This is an observational descriptive study of diagnosed SPNs confirmed histopathologically after surgical resections at Tribhuvan University Teaching Hospital (TUTH), Kathmandu, Nepal from 2006 November to 2019 January. Patient’s clinical details, surgical procedures, perioperative outcomes, and follow-up were recorded. Long-term follow-up was evaluated for a minimum of three years post-surgery. Results Over 13 years, a total of 15 cases with a median age of 22 years (11-52) were encountered and had female predominance (14). Five cases were diagnosed incidentally, while pain abdomen (five) was the most common presentation followed by lump (four). There were four tumors in the head of the pancreas, two in the uncinate process, two in the neck, four in the body, and three in the tail of the pancreas. Four cases underwent pancreaticoduodenctomy, three cases underwent enucleation, and four cases underwent central pancreatectomy. Similarly, one patient underwent spleen preserving distal pancreatectomy and three patients underwent distal pancretosplenectomy. Margins were negative in all cases with a median tumor size of six cm (2.5 -18). Postoperatively, 20% developed major complications with Clavien-Dindo (grade III & above) out of which one patient had mortality. Over the median follow-up of 72 months, no recurrences were noted. Conclusion Solid pseudopapillary neoplasms were relatively rare. Complete surgical resection was the most commonly used surgical management, post-operative complications were minimal and survival rate was excellent.